Between hospital and home – rehabilitation services for stroke survivors at a Western Cape Government-funded Transitional Care Facility - Rangolie, Carolyn (Stellenbosch : Stellenbosch University, 2026)
Thesis (MHumanRehabSt)--Stellenbosch University, 2025.